Pengolahan Citra dengan Segmentasi Thresholding untuk Pemilihan Kualitas Telur Asin - Nurhayati, Oky Dwi; Afifah, Diana Nur; ., Nuryanto; Rustanti, Ninik (Universitas Diponegoro, 2018)
Visually, choosing the quality of salted eggs by looking at egg shells is something that is very difficult to do. In addition, the lighting and the weakness of the senses of vision also becomes difficult to see the quality of salted eggs visually. So far, to determine a good salted egg, only known from the weight of eggs. Not all eggs that have mild density have poor quality. So far, suppliers often get eggs that have bad quality (broken) so that when processed will produce defective salted eggs. The goal achieved as an effort to improve the quality of this production is software design to know the quality of salted eggs. Quality selection technology involves image processing techniques such as gray imagery, histogram equalization, P-Tile segmentation, and first-order statistical feature extraction that serves to recognize the type of egg image quality. The results obtained with the application of image processing techniques have a fairly good accuracy to determine the quality of salted eggs into two good and bad conditions.Â Â